SOCIAL AND HYGIENIC STUDIES OF THE HEALTH OF CHILDREN BORN WITH HIGH BIRTH WEIGHT - Yuldasheva F. U.; Eshonkhodjaeva M. O.; Khojieva K. L.; Aliyev D. O.; Botirov O. Sh. (American Journals, 2024)
Children born with high birth weight are of particular interest for socio-hygienic research, since this factor can have a significant impact on their health and development. This abstract discusses the main aspects of social and hygienic research aimed at studying the health of such children. Factors influencing the risk of having high birth weight children are considered, such as the financial situation of the family, the mother's lifestyle and the environment. The health implications of high birth weight for children at various stages of their lives are also discussed, including the risk of obesity, cardiovascular disease and other pathologies.
Keywords: Children, newborns, overweight, pregnancy, hemolytic disease, overexposure, obesity.